Collecting duct renal cell carcinoma with the syndrome of inappropriate antidiuresis: An autopsy case report - Emi Yasuda (Indian Journal of Pathology and Microbiology, 2013)
A 57-year-old Japanese man visited our hospital with a moist cough. Chest radiographic imaging showed a left hilar shadow. Adenocarcinoma cells were found on cytologic screening of fresh sputum. Although multiple metastases including brain were detected, no tumor was observed in the kidneys. The patient underwent whole-brain irradiation and chemotherapy for advanced-stage lung cancer. One month before his death, carcinomatous meningitis was detected. Hyponatremia, hypo-osmolality, and hypertonic urine suggested the syndrome of inappropriate antidiuresis. Restricting water intake improved the hyponatremia; however, he developed fever and hematuria. Despite systemic administration of an antibacterial drug, he died. Primary tumor in the lung was absent, but adenocarcinoma of the right kidney was evident on autopsy. Lectin histochemical analysis of the carcinoma revealed its distal nephron origin, confirming collecting duct carcinoma. Severe carcinomatous meningitis, which is possibly caused the syndrome of inappropriate antidiuresis, was observed, with no cancer involvement of the pituitary gland and hypothalamus.